Innovative Approach to Financing Development in Africa: Crowdfunding - Christian Agbatchi Ode; Ajupov Ajdar Airativich; Jacob Afouda Yabi (International Journal of Supply Chain Management, 2022)
This paper has explored fundraising Africa’s development through crowdfunding. The study is based on the experience of a few platforms and on information from surveys and interviews with administrators of these platforms. It should be noted that crowdfunding is an alternative system to mobilize the financial resources for Small and Middle Enterprise, start-ups, associations and other organizations for the realization of any aimed goal. However, the main advantage of crowdfunding is the distribution of the project's risks among different contributors. This system of mobilizing resources could attract the diaspora and donors in financing Africa's development, if asymmetric information and moral risk linked to projects are controlled. In this article, it was found out that it is economically beneficial to finance development projects in African countries through crowdfunding, because it is less expensive than the capital market. Crowdfunding allows wide financing and could be allowed to raise donations, which is not possible on the capital market. It is also worth noting that this paper highlights the crucial role of crowd in monitoring funded development projects across the continent for efficiency.. Indeed, it has been proposed to set up a transaction management and monitoring committee to ensure their transparency.